FEATURES OF LINGUOPOETIC ANALYSIS OF LITERARY TEXT - Ahmadjonova Mahfuza (Galaxy International Interdisciplinary Research Journal, 2023)
The research carried out in the field of linguopoetics is the basis for determining its content structure. The existing theories and views are put into the system, as a result, the general direction of the direction is highlighted. The remaining issues form the basis of the research.